Muscle Cuff in Distal Pedicled Adipofascial Sural Artery Flaps: A Retrospective Case Control Study. Issue 3 (26th March 2021) - Schmidt, Karsten; Jakubietz, Michael Georg; Gilbert, Fabian; Fenwick, Annabel; Meffert, Reiner Heribert; Jakubietz, Rafael Gregor
Abstract : Background: Amputation after open tibial fracture occurs in 3% of cases. The rate increases when flap reconstruction is required. The standard care involves microsurgical tissue transfer although the pedicled reverse sural artery adipofascial flap (PRSAF) is a local alternative in patients endangered by a prolonged operative time. Incorporation of a gastrocnemius muscle cuff in this flap can be used to fill dead space and increase healing potential. Literature shows superior survival rates for both PRSAF and inclusion of a muscle cuff in comparison with the cutaneous version. The aim of the study was to compare the outcome of the PRSAF and the musculoadipofascial version (PRSMAF). We hypothesize that the PRSMAF provides similar lap viability and flap-related complication rates as does the adipofascial version. The muscle component may reduce the long-term osteomyelitis rate. Methods: Patients were evaluated retrospectively after reconstruction with either PRSAF or PRSMAF. Preoperative osteomyelitis, flap survival, complications and osteomyelitis clearance were analyzed. Results: The study shows preliminary results supporting the potential use of the PRSMAF. We compare either 23 PRSMAF or 20 PRSAF flaps. We found no statistically significant differences in flap survival or in complication rate. Conclusions: Although the anatomical situation may sometimes dictate the use of a free flap, a technically less-complicated option may in some cases offer a viable alternative. This study shows that the PRSMAF can serve as an alternative for complex bone defects in the limb, though it does not provide statistical improvement to the PRSAF.